A relação entre o projeto pedagógico e a aprendizagem dos alunos em escolas participantes do Projeto Geres em Belo Horizonte - Ana Maria Alves Saraiva (2009)
The main objective of this study is to investigate the relationship between the schools Political Pedagogical Project (PPP) and the level of growth in student learning. The research was conducted in four state government schools in Belo Horizonte, selected from among those participating in the GERES project, a panel- design, longitudinal research program to investigate learning progress among a cohort of students during the first four years of elementary school. Once the sample of schools was defined, through the use of a value-added learning criterion, the study was organized into three stages. The first involved the analysis of the PPP of each of the schools with the objective of gathering information on their development, content, compatibility with the theoretical assumptions and the official guidelines and the ability to guide classroom teaching activities. In the second stage, a questionnaire was applied to teachers to collect as to their participation in the drafting of their school PPP, their knowledge of the project and use made of in the classroom. The information supplied by the PPPs and the questionnaires were then related to the Value-added of the school, so see if the PPP could assist in explaining the differences observed between the schools regarding to level of progress of their students. The research concluded that the PPP follow standardized pattern, that they are not in agreement with the guidelines offered by the Secretariat of Education and do not reflect the specific characteristics of the schools. We failed to detect any relationship between the school PPPs and the level of learning of the students.